2010
DOI: 10.1088/0022-3727/44/1/015002
|View full text |Cite
|
Sign up to set email alerts
|

Coercivity enhancement in exchange biased CoO/Co3Pt bilayers

Abstract: A study on the exchange bias effect in an hcp (0002)-textured Co 3 Pt alloy film biased by a thin CoO film is presented. The Co 3 Pt film reveals an out-of-plane easy axis of magnetization although it was grown on an amorphous silica substrate at room temperature. Similar exchange bias fields measured in in-plane and out-of-plane directions of the CoO/Co 3 Pt bilayer system were observed for maximum cooling field. Whereas a pronounced cooling field dependence of the exchange bias field is observed in-plane, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, for applications, perpendicular uniaxial and unidirectional anisotropies are more desirable owing to a larger thermal stability of encoded information 23 . For instance, antiferromagnets in contact to ferromagnets with perpendicular anisotropy like Co/Pt multilayers and CoPt 3 layers have been shown to exhibit EB and all other macroscopic behaviour of EB systems, like training effect, enhanced coercivity and blocking temperature for the onset of the EB [23][24][25][26] . More recently, the perpendicular EB (PEB) was demonstrated in a novel exchange-coupled system Sm 1 − 0.028 Gd 0.028 Al 2 /SmAl 2 based on the zero magnetization ferromagnet Sm 1 − 0.028 Gd 0.028 Al 2 as the pinning layer 27 .…”
mentioning
confidence: 99%
“…However, for applications, perpendicular uniaxial and unidirectional anisotropies are more desirable owing to a larger thermal stability of encoded information 23 . For instance, antiferromagnets in contact to ferromagnets with perpendicular anisotropy like Co/Pt multilayers and CoPt 3 layers have been shown to exhibit EB and all other macroscopic behaviour of EB systems, like training effect, enhanced coercivity and blocking temperature for the onset of the EB [23][24][25][26] . More recently, the perpendicular EB (PEB) was demonstrated in a novel exchange-coupled system Sm 1 − 0.028 Gd 0.028 Al 2 /SmAl 2 based on the zero magnetization ferromagnet Sm 1 − 0.028 Gd 0.028 Al 2 as the pinning layer 27 .…”
mentioning
confidence: 99%
“…The exchange bias effect generally occurs under the field cooling (FC) conditions. 16,17,[19][20][21][22][23][24] In the present study, however, a horizontal shift of the hysteresis loop is hardly observed for the FM and AFM bilayers (Fig. S12 in the ESI †).…”
Section: Resultsmentioning
confidence: 69%
“…1,15 Recently, the coercivity and remanence of ferro-and ferrimagnetic (FM) materials have been found to be controlled by exchange coupling, such as exchange bias effects. [16][17][18][19][20][21][22][23][24][25][26] Since a combination of FM and antiferromagnetic (AFM) materials enhances the coercivity of magnetic nanoparticles and thin films, specific core-shell and layered structures have been designed to improve their magnetic properties. [16][17][18][19][21][22][23][24][25] However, precise control of the lattice constants by adjusting the preparation conditions is required to form suitable interfaces between FM and AFM materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation